Vivência da família : o cuidado no domicílio a um familiar com incapacidades decorrentes de um acidente vascular encefálico - Misawa, Fernanda (2015)
The cerebrovascular accident has great epidemiological importance, being the second cause of death and the main cause of acquired disability in the world. Statistics show that about 40% of the survivors of a Cerebrovascular Accident have some level of disability becoming dependent on care. Faced with the need for assistance, the family is usually who takes care of the family sick member, being his primary provider of care. This study aimed to understand the experience of family home care to the adult with disabilities due to Cerebrovascular Accident, after hospital discharge. It is an intervention, descriptive study, with a qualitative approach, using as theoretical reference the Calgary Model of Family Assessment and Convergent Healthcare Research methodology. It was held in the municipality of Maringá, Sarandi and Marialva with members of four families who live the experience of caring for a family member with disabilities due to Cerebrovascular Accident. The families approach was during the hospitalization, and data collection occurred through home visits to every family, in the months of February to September 2014. During the visits informal interviews and semi-structured, and participant observation were also conducted. All families were monitored at least once a week, until four months after hospital discharge. The assistance provided to families was determined by the needs emerging in every meeting and covering activities such as guidance and clarification of doubts for all family members, care and procedures demonstration for the main caregiver and direct care to the sick family member. It was observed that the chronic disease causes changes in routine, in the roles, on the financial situation, overload of caregivers, in many cases intensification and/or appearance of conflicting relationships, and to live with a sick family member with disabilities after hospital discharge, requires that families organize and adapt for care at home, involving a series of changes in functions and in the roles that each member exerts on the family unit. The nursing care subsidized the family, to adapt to this new reality, to identify their strengths and weaknesses, to seek strategies for coping and problem-solving emergency during the experience of care, and thus the researcher and family choose the priorities for planning care.